Identificação de forças excitadoras a partir das respostas dinâmicas no domínio do tempo - Genaro, Gino (1997)
This work addresses the problem of indirect force reconstruction employing time-domain-based techniques. In this context, two methods are examined. The first method proposed, named "Modal Coordinate Technique", explores the modal equilibrium equations and utilizes the acceleration time histories as well as a set of eigensolutions of the structure (natural frequencies, modal damping factors, generalized masses and eigenvector components). The second method, named "Deconvolution Technique" is based on the deconvolution of the acceleration time histories, requiring a set of impulse response functions of the structure. After the formulation of both methods are presented they are evaluated through several applications performed on a numerically simulated test-structure. Based on the obtained results, it is possible to evaluate the performance and major characteristics of both methods. In particular, attention is paid to the effects of the incompleteness of the data and experimental noise upon the performance of the methods.